The Evolution of Talent Development Programs in Academic Literature: A Bibliometric Review - Mohammad Gifari Sono; Diputra, Gede Bagus Wira (Eastasouth Institute, 2024)
This study conducts a comprehensive bibliometric analysis of the evolution of talent development research, mapping its key themes, influential authors, and geographic collaborations from 1952 to 2024. Using data from Google Scholar and VOSviewer, the analysis identifies central themes such as